2002
DOI: 10.1002/jmv.10287
|View full text |Cite
|
Sign up to set email alerts
|

Genome types of adenovirus type 7 isolated in Hiroshima City

Abstract: One hundred thirty-two strains of adenovirus type 7 were isolated in Hiroshima City during the period 1995-1999. About 80% of the viruses were isolated from patients with respiratory illness, and about 70% were isolated from children younger than 6 years old. DNA restriction analysis was performed on 58 of the 132 isolates. Two genome types corresponding to adenovirus 7d and adenovirus 7h were recognized using BamHI. By using an additional 10 restriction endonucleases (BclI, BglI, BglII, BstEII, HindIII, HpaI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…But HAdV7, a member of the B1 subspecies, has been identified in epidemics to be highly virulent and is associated with clinical manifestations of considerable severity, including residual lung damage and fatal outcomes (810). This pathogen has been found in outbreaks in the United States and Asia and has become a global concern (1113). It also poses a special threat for infants and young children as their immune systems are not completely established.…”
Section: Genome Announcementmentioning
confidence: 99%
“…But HAdV7, a member of the B1 subspecies, has been identified in epidemics to be highly virulent and is associated with clinical manifestations of considerable severity, including residual lung damage and fatal outcomes (810). This pathogen has been found in outbreaks in the United States and Asia and has become a global concern (1113). It also poses a special threat for infants and young children as their immune systems are not completely established.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Although a higher virulence of HAdV7h was indicated during these outbreaks, there is no virological evidence to indicate increased virulence of HAdV7h. Outside of South America, HAdV7h was first identified in Japan in 1996 and then in the US in 1998 (5,9,23).…”
mentioning
confidence: 99%
“…Recent molecular epidemiology studies have shown that the most prevalent strains of HAdV-B1 isolated from cases of acute respiratory disease encode versions of ORF E3-10.9K that contain truncating or null mutations [10,37,38] suggesting the existence of a selective advantage for loss of this gene among pathogenic HAdV-B1s. Interestingly, the genomes of HAdV-B2s appear to be naturally occurring deletion mutants for this ORF [39-41].…”
Section: Discussionmentioning
confidence: 99%